Evaluating the suitability of the Perceive, Recall, Plan and Perform System of Task Analysis (PRPP‐A) for assessing work‐related cognitive difficulties in women after breast cancer: A comparison with Cambridge Neuropsychological Test Automated Battery (CANTAB) - Lewis, Joanne; Mackenzie, Lynette; Chapparo, Chris; Ranka, Judy (Australian Occupational Therapy Journal, 2026)
Introduction: An increasing number of working‐age women are diagnosed with breast cancer, making it critical to understand cognitive difficulties that may affect their work performance. This pilot study aimed to evaluate the suitability of the Perceive, Recall, Plan and Perform System of Task Analysis Assessment (PRPP‐A) for occupational therapists assessing work performance after breast cancer, by examining its alignment with domain‐specific cognitive measures obtained from the Cambridge Neuropsychological Test Automated Battery (CANTAB) and its capacity to identify cognitive difficulties relevant to work tasks. Methods: The pilot study involved 12 women diagnosed with breast cancer who were employed at the time of diagnosis. Participants completed cognitive assessments using the PRPP‐A (administered via semi‐structured interview) and computerised CANTAB subtests, including Rapid Visual Processing (RVP), Delayed Matching to Sample (DMS), and Spatial Working Memory (SWM). Associations between CANTAB subtests and corresponding PRPP‐A quadrants were examined, and the ability of PRPP‐A and CANTAB scores to predict work participation outcomes was explored. Consumer and Community Involvement: Women were recruited through Breast Cancer Network Australia (BCNA). The study was advertised on the BCNA website, and a national webinar was conducted to encourage participation. Results: The PRPP‐A showed difficulties in the following items: Continuing (mean = 47.08, SD = 17.464), Initiating (mean = 56.92, SD = 13.118), Attending (mean = 58.25, SD = 15.428) and Programming (mean = 59.42, SD = 11.204). Significant correlations were found between PRPP‐A Total Perceive and CANTAB RVP (τ = 0.477, P = 0.036) and PRPP‐A Total Plan and CANTAB SWM (τ = −0.735, P = 0.002). Receiver operating characteristic (ROC) analysis showed that PRPP‐A Total Cambridge Neuropsychological Test Automated Battery Perceive scores were the only testing component to predict both nonreturn to pre‐cancer roles (area under the curve [AUC] = 0.969) and hours of work (AUC = 0.719). PRPP‐A Total Plan (AUC = 0.734) and CANTAB RVP Detecting Signal test (AUC = 0.750) demonstrated acceptable sensitivity for predicting women not returning to pre‐cancer roles. Conclusion: The PRPP‐A demonstrated suitability as a cognitive assessment for occupational therapists by aligning with domain‐specific neuropsychological measures while identifying work‐relevant functional cognitive difficulties. Its occupation‐focussed, ecologically valid approach supports clinical use in assessing work performance after breast cancer, although confirmation in larger samples is required PLAIN LANGUAGE SUMMARY: Many working‐age women are diagnosed with breast cancer, and it is important to understand how this affects their ability to work. This pilot study looks at how breast cancer impacts cognitive functions (like memory and attention) and work performance. It compares two assessment tools: the PRPP‐A System of Task Analysis and the CANTAB tests. The study involved 12 women who had breast cancer and were working when diagnosed. They took part in cognitive tests using both PRPP‐A and CANTAB methods. These tests included tasks to measure attention, memory, and planning skills. Women were recruited through Breast Cancer Network Australia (BCNA) and participated voluntarily. The study was promoted on the BCNA website and through a national webinar. The results showed that many participants had significant cognitive difficulties, especially with attention, memory, and planning. The PRPP‐A identified specific challenges like continuing tasks, starting tasks, paying attention, recalling facts, and planning. These findings matched previous studies. The study also found that PRPP‐A and CANTAB scores were closely related, meaning both tools measured similar cognitive skills. The PRPP‐A scores were particularly good at predicting which women struggled to return to their pre‐cancer work roles. The PRPP‐A may be effective for assessing cognitive difficulties in breast cancer survivors and works well with neuropsychological tests. Using PRPP‐A in regular practice could help create personalised interventions to address specific cognitive issues, especially those related to attention and planning, and in turn improve work outcomes for breast cancer survivors. Future research should involve more participants and include employers to validate PRPP‐A findings and add an environmental perspective to the assessment.